Rancang Bangun Timbangan Buah Digital Menggunakan Metode YOLO - Riza Alfita; Rosida Vivin Nahari; Miftachul Ulum; Mirza Pramudia; Clarisna Evita; Haryanto Haryanto (Jurnal FORTECH, 2022)
The rapid development of technology has created various conveniences in all aspects of human life. One of the fields of technology that is rapidly developing is the world of electronics, which demands digitization to facilitate human activities. For example in the field of trade, humans want a process that is practical and easy. Weight measurement is one of the problems that hinders the trading process, because it is still done manually and is less efficient. The purpose of making a design of automatic digital scales based on fruit images using the yolo method (you only look once) is to determine the type and weight of fruit using a Load Cell sensor simultaneously and accurately. The working principle of this tool is the first, the detection of fruit types is processed by a USB Webcam by taking video from the Webcam and then processing it using the Yolo method to identify the type of fruit. The second stage is input from the Load Cell sensor sending object data read to the Raspberry Pi as the main controller. to determine the weight of the fruit, then the last stage is displayed on the LCD and the results can be printed out as proof of purchase receipt. From the LCD directly displays output in the form of price, weight and type of object being weighed. The Yolo method can detect objects and colors and has high detection speed and accuracy.